Case Report: Transfusion-associated graft-versus-host disease in severe combined immunodeficiency - Jiang, Chunxue; Sun, Tingting; Xu, Xuewen; Xu, Wei; You, Kai (Frontiers in Immunology, 2026)
Transfusion-associated graft-versus-host disease (TA-GVHD) is a rare but fatal blood transfusion complication, with a mortality rate of 90-100%. Severe combined immunodeficiency (SCID) is a life-threatening primary immunodeficiency with profound cellular and humoral defects. Patients with SCID are highly susceptible to TA-GVHD. Here, we report a 4-month-old male admitted for sepsis and severe pneumonia, with pustular rash and unhealed exudative Bacillus Calmette-Guérin vaccination site. Laboratory tests showed hypogammaglobulinemia and lymphopenia. Lymphocyte subset analysis confirmed the presence of T-B+NK immunodeficiency. Mycobacterium bovis complex was detected in blood, while rifampicin-resistant Mycobacterium tuberculosis complex was identified in sputum and ascitic fluid. Whole-exome and Sanger sequencing identified a novel interleukin-2 receptor common gamma chain (IL2RG) nonsense mutation [NM_000206.3: c.865C>T, p.(Arg289Ter)]. To the best of our knowledge, this specific IL2RG mutation has not been previously reported. On the 33rd day of admission, the infant accidentally received non-irradiated leucoreduced red blood cells, then developed typical TA-GVHD manifestations including fever, hepatomegaly, rash and diarrhea, and high-resolution Human Leukocyte Antigen typing confirmed it. The parents chose to terminate treatment on the 69th day of admission, and the patient died after discharge. The dynamic evolution of clinical manifestations and laboratory tests in this patient is described, along with a review of the relevant literature. This report expands the mutational spectrum of IL2RG and reveal the reference value of peripheral blood lymphocyte and eosinophil counts for early TA-GVHD identification.